On some cardinal invariants of space of finite subsets - Praninskas, Gintaras (Lietuvos matematikos rinkinys, 2005)
In article is investigated relationships between some cardinal invariants of topological space and it’s space of finite subsets with Vietoris topology. In generalwe note coincidence of them.
Keywords: topological space; Vietoris topology; hyperspace; the space of finite subsets